Rendimiento académico y estrés en estudiantes de postgrado de ortodoncia de una universidad colombiana (2020)
INTRODUCTION: Young people entering higher education programs, undergo a change in their lives that requires greater commitment and dedication because they are subjected to new demands imposed by a greater academic burden and new responsibilities during their university years. OBJECTIVE: To explore from a mixed quantitative and qualitative approach, the academic performance of a group of dentistry graduate students in a Colombian University. METHODS: The sampling was intentional because of the accessibility that was available since they were students of the University; From a quantitative component, information was collected on the state of the stress situation, through the "Stress Assessment Questionnaire" survey and a qualitative component based on the focus group strategy. RESULTS: The average age of the students was 30.24 ± 4.78 years, with a high level of stress in 31.2% of the respondents, and very high in 32.35%. From a qualitative point of view, the students expressed the way in which the academic load occupies important spaces in their daily lives that end up affecting their states of health. CONCLUSIONS: The early identification of stress factors among graduate students in dentistry can help to enhance coping strategies and assist in the design of programs that ensure better academic performance and improve the quality of life of students.